2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354040
|View full text |Cite
|
Sign up to set email alerts
|

3D human modeling using virtual multi-view stereopsis and object-camera motion estimation

Abstract: Abstract-This paper presents a method for multi-view 3D modeling of human bodies using virtual stereopsis. The algorithm expands and improves the method used in [5], but unlike that method, our approach does not require multiple calibrated cameras and/or carefully-positioned turn tables. Instead, an algorithm using SIFT feature extraction is employed and an accurate motion estimation is performed to calculate the position of virtual cameras around the object. That is, by employing a single pair of cameras moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Since the main application for our camera rig is for 3D object modeling, we tested the accuracy of the calibration by reconstructing a sphere based on the idea of visual hull (Laurentini, 1994) and the human body using an algorithm for multi-view 3D modeling presented in (Lam et al, 2009). As before, the tests were conducted for both synthetic data and real data.…”
Section: D Object Modelingmentioning
confidence: 99%
“…Since the main application for our camera rig is for 3D object modeling, we tested the accuracy of the calibration by reconstructing a sphere based on the idea of visual hull (Laurentini, 1994) and the human body using an algorithm for multi-view 3D modeling presented in (Lam et al, 2009). As before, the tests were conducted for both synthetic data and real data.…”
Section: D Object Modelingmentioning
confidence: 99%
“…Its high-end, 6-figure cost makes it definitely not appropriate for self monitoring. Technologies for 3D reconstruction for human bodies and other objects have been around for many years [14], [15], [16], [17], [18], [19], [20], [21]. They provide very accurate and reliable models, which can be used for measuring limb volumes with equal or better accuracy than the methods used today.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a topic currently in high demand, 3D modeling of the human body poses a great challenge and while earlier approaches employing multi-view stereopsis [17], [18], [19], [20] could build reasonable 3D models from simple 2D images, they were also not as reliable as newer methods based on new IR sensing technologies. Besides, they required well calibrated cameras [17], [18] and some times, a setup of multiple cameras [19], [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that having an affine transform matrix was shown to outperform features matching in recognizing object orientations. Another method employing the SIFT feature extraction was presented by Lam et al (2009). The authors implemented virtual stereopsis in 3D modeling of human bodies without the use of multiple calibrated cameras.…”
Section: Introductionmentioning
confidence: 99%